Anemia among pregnant women attending primary healthcare units in the municipality of São Paulo, Brazil: evaluations after the mandatory fortification of wheat and maize flours with iron. Issue 1 (December 2016) - Machado, Edna; De Carli, Eduardo; Szarfarc, Sophia; Souza, José; Fujimori, Elizabeth; Colli, Célia
Abstract Background Improvements in the iron status of a population as result of food fortification are expected at the long term. In Brazil, the effectiveness of mandatory flour fortification with iron has been evidenced mostly from surveys on gestational anemia after 1 or 2 years from its implementation, in 2004. Our aim was to assess hemoglobin (Hb) concentrations and the prevalences of anemia and linked erythrocyte morphology patterns among pregnant women in 2006 and 2008. Methods The study design was retrospective and cross-sectional. The analysis was based on secondary data in 546 medical records from women at the times of their first prenatal attendance in 13 public primary healthcare units of the Butantan Administrative Region from São Paulo (SP), Brazil. Anemia was evaluated from Hb concentration (cut-off <11.0 g/dL) and erythrocyte morphology patterns from mean corpuscular volume (MCV), mean corpuscular Hb concentration (MHC), and red cell distribution widths (RDW). Recorded sociodemographic and obstetric data included maternal age, gestational age, ethnoracial self-classification, and residence type. Student'st tests, analysis of variance, Chi-squared tests, and multiple linear and logistic regressions were employed in the statistical analysis using a significance level of 5 %. Results The prevalence of anemia was 9.7 % in 2006 and 9.4 % in 2008 (P  = 0.922), with no significant difference in mean Hb concentrations (P  = 0.159). Normocytosis (normal MVC), normochromia (normal MHC), and anisocytosis (high RDW) were found in most anemia cases, suggesting that the low Hb concentrations resulted from mixed causes. In multiple regression analysis, gestational age at the first prenatal attendance was an independent predictor of low Hb and of having anemia. Moreover, black ethnoracial self-classification was associated with lower Hb. Conclusions The prevalence of gestational anemia was low among women in both of the studied periods, representing a mild public health problem. Our results highlight the importance of early prenatal care as a means of reducing gestation-associated risks. The erythrocyte morphology pattern found in most cases of low Hb levels suggests that, besides iron deficiency, hemoglobinopathies and nutritional deficiencies of folate and vitamin B12 are common complicating factors of gestational anemia in our setting.